Phylogenetic relationships within the genus Cynanthus (Aves: Trochilidae), with emphasis on C. doubledayi - García-Deras, Gabriela M.; Cortés-Rodríguez, Nandadevi; Honey, Magali; Navarro-Sigüenza, Adolfo G.; García-Moreno, Jaime; Hernández-Baños, Blanca E. (Zootaxa, 2008)
We investigated the phylogeny of the genus Cynanthus and the taxonomic status of C. doubledayi using partial sequences of the mitochondrial DNA gene ND2 and three phylogenetic approaches: maximum parsimony, maximum likelihood, and Bayesian inference. Our results corroborate the monophyly of the genus and provide preliminary support for the validity of C. doubledayi as a full species (not a subspecies of C. latirostris, as traditionally considered). As an endemic of the coastal plain of southwestern Mexico, C. doubledayi corroborates the importance of this region for in situ speciation of birds and other taxa.